Beyond thermal comfort in the hospital rooms. Investigation of thermal summer comfort in patients rooms: case of Biskra hospitals - Besbas, Yasmina; Zemmouri, Nourdinne (Journal of Applied Engineering Science & Technology, 2018)
In Algeria, the architectural design of hospitals is unfortunately not subject to clear and specific regulatory thermal strategy, it depends mainly on the architect own approach to the issue of comfort design, materials, etc. This research aims to investigate the present comfort conditions in typical hospital configuration and under specific climate conditions of hot and arid regions. Two different hospital designs have been investigated in Biskra. A main town is southeast of Algeria. The first case study being the oldest hospital in the town, build in the late 30s during the colonial era and renovated recently. The second hospital is a brand new hospital. A series of measurements of ambient air temperature, patient surveys and interviews have been initiated in two typical wards. The results show that thermal comfort sensations in these specific spaces depend not only on architecture, design and typical processes, but also on physiological, psychological and behavioral parameters which widely influence the perception of the patients.